Serum free triiodothyronine is inversely associated with diabetic peripheral neuropathy but not with carotid atherosclerotic lesions in euthyroid patients with type 2 diabetes - Mei-Fang Li (BMC, 2021)
Abstract Background The associations between serum free triiodothyronine (FT3) and diabetic peripheral neuropatprohy (DPN)/carotid atherosclerotic lesions in euthyroid patients with type 2 diabetes are still unclear. The purpose of our study was to explore the relations of FT3 to DPN and carotid atherosclerotic lesions in Chinese type 2 diabetes inpatients with euthyroid function. Methods 2477 euthyroid inpatients with type 2 diabetes were recruited and they were stratified into quartiles by FT3 levels in this cross-sectional study. Peripheral neuropathy was assessed by neurological symptoms and signs as well as nerve conduction velocity tests. Carotid atherosclerotic lesions, including carotid intima-media thickness, plaque and stenosis, were evaluated by Doppler ultrasound. Results The prevalence of DPN in type 2 diabetic patients exhibited the significant decrease across the FT3 quartiles (23.5%, 20.9%, 18.8%, and 11.2%, respectively, p < 0.001). Multiple logistical regression analysis also revealed that FT3 quartiles were significantly and inversely associated with DPN. Compared with the subjects in the highest FT3 quartile, the adjusted odds ratios (95% confidence interval) of DPN from the first to third FT3 quartile were successively 2.338 (1.407–3.884), 1.903 (1.134–3.194) and 1.598 (0.960–1.125). The patients with DPN had significantly higher prevalence of carotid atherosclerotic lesions compared with non-DPN patients. However, no statistical association was observed between FT3 quartiles and carotid atherosclerotic lesions after adjusting for confounder factors. Conclusions Lower FT3 within the normal range was independently associated with DPN, but not with carotid atherosclerotic lesions in Chinese euthyroid inpatients with type 2 diabetes.